Role of Mitochondria-Derived Damage-Associated Molecular Patterns associated to extracellular microvesicles in promoting early microglia-mediated pro-inflammatory response in neurodegenerative disorders - Tavares, Henrique Rafael Freitas (2022)
Trabalho de Projeto do Licenciatura em Engenharia Biomédica apresentado à Faculdade de Ciências e Tecnologia